2018
DOI: 10.1002/ghg.1838
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Bragg grating‐based experimental and numerical investigations of CO2 migration front in saturated sandstone under subcritical and supercritical conditions

Abstract: Carbon dioxide (CO2) can be at risk of leakage during its storage in deep saline aquifers due to stress field changes in the reservoir. The aim of this study was to investigate the effects of CO2 injection pressure on dynamic strain response of the reservoir and the CO2 migration process. A series of core flooding experiments was performed with the‐state‐of‐art fiber Bragg grating sensors. The results show that the surface strain response was linearly correlated with CO2 injection pressure. Carbon dioxide migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In a previous study, we used DFOSS to monitor the migration of a CO 2 plume in rocks, particularly for the underground storage of CO 2 (Zhang et al, 2019). Fan et al (2019) applied the quasi-distributed fiber Bragg grating sensing method (with three monitoring points) to detect the front of a CO 2 plume.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we used DFOSS to monitor the migration of a CO 2 plume in rocks, particularly for the underground storage of CO 2 (Zhang et al, 2019). Fan et al (2019) applied the quasi-distributed fiber Bragg grating sensing method (with three monitoring points) to detect the front of a CO 2 plume.…”
Section: Introductionmentioning
confidence: 99%
“…Equations COMSOL TM can be used to simulate migration characteristics of two-phase flow in porous media by the finite element method and many researchers have done similar work in this area. [26][27][28] Typically, multiphase flow in porous media multiphysics interface is used to simulate immiscible displacement processes in which the two physical fields of phase transport in porous media and Darcy's law are coupled. 29 The basic mass conservation equations for two-phase immiscible flow without considering gravitational effects are listed as follows:…”
Section: Methodsmentioning
confidence: 99%
“…However, the strain response is a direct reflection of fluid injection stress and migration front within pore structure. For example, Fan et al (2019) performed a series of core flooding experiments monitored by fiber Bragg grating (FBG), and they found that surface strain response of rock was linearly correlated with CO 2 injection pressure and CO 2 migration could be monitored by FBG. Xu et al (2022) experimentally investigated the CO 2 leakage process along fault rock, and the result found that the small strain induced by leakage stress could be monitored by FBG.…”
Section: Dissolution and Deformation Characteristics Of Limestones Co...mentioning
confidence: 99%